Effect of beam ellipticity on femtosecond laser multi-filamentation regulated by π-phase plate. (7th July 2020) - Liu, Jinpei; Tian, Xianqing; Chu, Chunyue; Sui, Heliang; Zhang, Zhi; Liang, Dong; Zhang, Nan; Lin, Lie; Liu, Weiwei
Abstract: The regulation of multiple filaments during an intense femtosecond laser propagation in a transparent optical medium is still challenging. In this study, by tracing the phase variation of the laser pulse during the propagation, the effect of the beam ellipticity on the generation of multiple filaments was investigated using the efficient π -phase plate. The spatial distribution of the generated multiple filaments did not follow the predesigned pattern of the phase plate when the laser beam was elliptic owing to the asymmetric change of the laser phase by the linear diffraction and nonlinear Kerr effect.